Sistem Pakar Untuk Mendiagnosa Kerusakan Smartphone Dengan Metode Forward Chaining Berbasis Web - Akbar, Nur Charisma; Sylviana, Felicia; Saputra, Ade Chandra (Journal of Information Technology and Computer Science, 2021)
So far, smartphone users who experience damage to their smartphones tend to have difficulty or confusion in dealing with the damage they have experienced, they tend to be confused and without thinking Long immediately submit it to service providers, this method is indeed effective but has a bad impact on users because they don't know the chronology of the damage. what happens on their smartphone, as a result users can be fooled, cheated, or get unilateral treatment that is detrimental to the user, from this problem the author wants to offer a solution by using an expert system application that aims to describe the solution to the damage that occurred and educate the damage that occurred.The expert system to diagnose damage to this smartphone uses the forward chaining method, the programming languages used are PHP, CSS and Java Script, the program functionality design process uses Flowcharts, Data Flow Diagrams and Entity Relationship Diagrams and designs the program's User Interface Design, and the stages of its manufacture using the waterfall metrology, which in its development has several sequential stages: requirements (needs analysis), system design (system design), Coding & Testing, Program implementation, maintenance. Testing the expert system to diagnose damage to this smartphone uses blackbox testing techniques. Based on the results of research, analysis, design, to the results of making this expert system, it can be concluded that the test results are appropriate and meet the conditions that are expected to develop by adding new types of damage that can increase the diversity of data in the database so as to produce programs that can run properly. namely in the form of an application to diagnose smartphone damage based on the symptoms of the damage that occurred.